The Kap60-Kap95 Karyopherin Complex Directly Regulates Phosphatidylcholine Synthesis - MacKinnon, Melissa A. (American Society for Biochemistry and Molecular Biology, 2009)
Phosphatidylcholine is the major phospholipid in eukaryotic cells. There are two main pathways for the synthesis of phosphatidylcholine: the CDP-choline pathway present in all eukaryotes and the phosphatidylethanolamine methylation pathway present in mammalian hepatocytes and some single celled eukaryotes, including the yeast Saccharomyces cerevisiae. In S. cerevisiae, the rate-determining step in the synthesis of phosphatidylcholine via the CDP-choline pathway is catalyzed by Pct1. Pct1 converts phosphocholine and CTP to CDP-choline and pyrophosphate. In this study, we determined that Pct1 is in the nucleoplasm and at endoplasmic reticulum and nuclear membranes. Pct1 directly interacts with the α-importin Kap60 via a bipartite basic region in Pct1, and this region of Pct1 was required for its entry into the nucleus. Pct1 also interacted with the β-importin Kap95 in cell extracts, implying a model whereby Pct1 interacts with Kap60 and Kap95 with this tripartite complex transiting the nuclear pore. Exclusion of Pct1 from the nucleus by elimination of its nuclear localization signal or by decreasing Kap60 function did not affect the level of phosphatidylcholine synthesis. Diminution of Kap95 function resulted in almost complete ablation of phosphatidylcholine synthesis under conditions where Pct1 was extranuclear. The β-importin Kap95 is a direct regulator membrane synthesis.